AKTIVITAS MAHASISWA DALAM MEMBACA SKRIPSI DI PERPUSTAKAAN FISIP UNS - Masriyatun Masriyatun (Jurnal Pustaka Ilmiah, 2016)
Libraries in general most people say that as a place to read and borrow librarycollections, where the librarian or library manager provides various types of services. Services that can be said to be superior and excellent, in the library Fisip UNS contained in the reference collection service because the place is never empty by the reader. Readers in this space the average reader of scientific work, such as theses and other types of research. The purpose of writing this article to determine the activity of students in reading thesis. Activities of students in reading this paper are used to meet the information needs in the manufacture of scientific work. This research method using descriptive method. Location of the study in the library Fisip UNS. The results of this study indicate that the activity of students in reading thesis categorized quite high as 30 or 60% of respondents said it was.